2015
DOI: 10.3390/membranes6010004
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Microporous Polymeric Support Modification on Surface and Gas Transport Properties of Supported Ionic Liquid Membranes

Abstract: Microporous polymers based on anionic macroinitiator and toluene 2,4-diisocyanate were used as a support for 1-butyl-3-methylimidazolium hexafluorophosphate ([bmim][PF6]) and 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide ([emim][Tf2N]) immobilization. The polymeric support was modified by using silica particles associated in oligomeric media, and the influence of the modifier used on the polymeric structure was studied. The supported ionic liquid membranes (SILMs) were tested for He, N2, NH3, H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 64 publications
0
24
0
Order By: Relevance
“…As a preliminary study, the gas transport characteristics were determined and the ideal and apparent (effective) selectivities of the MDK-3 membrane and the symmetric membrane based on quaternized chitosan were calculated. The permeability of individual gases was measured by the Daynes-Barrer time lag method [36,37] detailed in previous papers of the authors [38][39][40]. To determine the permeability of the components of the gas mixture and calculate the effective selectivity of the MDK-3 membrane, the gas chromatographic method was used as described in detail in [41,42].…”
Section: Methodsmentioning
confidence: 99%
“…As a preliminary study, the gas transport characteristics were determined and the ideal and apparent (effective) selectivities of the MDK-3 membrane and the symmetric membrane based on quaternized chitosan were calculated. The permeability of individual gases was measured by the Daynes-Barrer time lag method [36,37] detailed in previous papers of the authors [38][39][40]. To determine the permeability of the components of the gas mixture and calculate the effective selectivity of the MDK-3 membrane, the gas chromatographic method was used as described in detail in [41,42].…”
Section: Methodsmentioning
confidence: 99%
“…This clearly indicates the capping of MNP has increased the stability of the MNP compared to bare MNP under acidic condition used for regeneration. Such high stability of MNP after capping might be due to the resistance to the permeability of Fe(III) as starch and casein capping acts as support material and prevents leaching of Fe(III) ions . Furthermore, casein and starch support also plays an important role in avoiding air void that decreases adsorption efficiency of nano‐adsorbents .…”
Section: Resultsmentioning
confidence: 99%
“…Such high stability of MNP after capping might be due to the resistance to the permeability of Fe(III) as starch and casein capping acts as support material and prevents leaching of Fe(III) ions. [68][69][70] Furthermore, casein and starch support also plays an important role in avoiding air void that decreases adsorption efficiency of nano-adsorbents. [68][69][70] Hence, we confirmed that both MNP ST and MNP CS posses better potential as nano-adsorbents with excellent regeneration capacity compared to MNP towards removal of heavy metals from contaminated water for a number of cycles.…”
Section: Regeneration and Reusability Studymentioning
confidence: 99%
“…SILMs is one of the most attractive methods for separating CO 2 from gas mixture. It is the first solution proposed that combining the excellent properties of ILs and polymer membranes together . Resembled to traditional amine‐based aqueous solvents, ILs were immobilized in porous membranes to act as the liquid separating phase materials.…”
Section: Co2 Capture and Separation By Ionic Liquids‐based Membranesmentioning
confidence: 99%
“…It is the first solution proposed that combining the excellent properties of ILs and polymer membranes together. [23,24,25] Resembled to traditional aminebased aqueous solvents, ILs were immobilized in porous membranes to act as the liquid separating phase materials. The incorporation of ionic liquids enhanced the stabilization as ILs have negligible vapor pressure and relatively high viscosity (resistance to leaking-out by high pressure differentials).…”
Section: Supported Ionic-liquid Membranes (Silms)mentioning
confidence: 99%